2017
DOI: 10.7759/cureus.1700
|View full text |Cite
|
Sign up to set email alerts
|

Acute Brachial Artery Occlusion in an Elderly Patient With Acute Myocardial Ischemia

Abstract: We present a case of left upper extremity paresis secondary to acute brachial artery occlusion in an elderly female with active non-ST segment elevation myocardial ischemia (NSTEMI) in the setting of paroxysmal atrial fibrillation. The patient was initially suspected to have a cerebrovascular attack (CVA); however, computed tomography (CT) head was negative for acute stroke. The diagnosis was confirmed by computed tomographic angiography (CTA) of the upper extremity, confirming the diagnosis of acute left brac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…3,4 Several studies have identified upper extremity arterial occlusions after coronary catheterization; however, there are few reports of unprovoked brachial artery occlusion. 1,5,6 When considering brachial artery occlusion in patients, the diagnostic workup should include a thorough physical exam, point-of-care ultrasound (POCUS), and coagulation laboratory studies. 7 A computed tomography (CT) angiogram Creighton University School of Medicine, Department of Emergency Medicine, Phoenix, Arizona Mayo Clinic, Department of Emergency Medicine, Phoenix, Arizona * † can be considered if POCUS and clinical exam are insufficient to provide this time-sensitive diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Several studies have identified upper extremity arterial occlusions after coronary catheterization; however, there are few reports of unprovoked brachial artery occlusion. 1,5,6 When considering brachial artery occlusion in patients, the diagnostic workup should include a thorough physical exam, point-of-care ultrasound (POCUS), and coagulation laboratory studies. 7 A computed tomography (CT) angiogram Creighton University School of Medicine, Department of Emergency Medicine, Phoenix, Arizona Mayo Clinic, Department of Emergency Medicine, Phoenix, Arizona * † can be considered if POCUS and clinical exam are insufficient to provide this time-sensitive diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Acute limb ischemia affects approximately 10–14 patients per 100,000 annually and more commonly occurs in the lower extremities. 1 , 2 The brachial artery is located in the upper extremities and is commonly used to measure blood pressure. Acute embolization of the brachial artery is most commonly cardiac in origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation